Stenosis of the right major bronchus from blunt trauma - Stanić Vojkan; Vulović Tatjana; Durković Savo; Cvijanović Vlado; Ristanović Aleksandar; Gulić Bojan; Stamenović Davor (Vojnosanitetski Pregled)
Background. A severe blunt injury to the chest might cause rupture of the tracheobronchial tree. A certain time following the management of the injury, stenosis of the bronchi may develop at the site of the rupture. Case report. We reported a patient injured in a traffic accident. The injury was followed by the signs of pneumothorax, bleeding, and respiratory insufficiency. After the management of the injury using thoracal drainage, the condition of the injured was stabilized. Two weeks later, however, difficulties in breathing and fatigue occurred. Circular stenosis of the right major bronchus was clinically, radiographically and bronchoscopically confirmed. Right thoracotomy and circular resection of the major bronchus with termino-terminal anastomosis were performed. Conclusion. In severe blunt injuries to the chest, it is very important to suspect the injury of the tracheobronchial tree in order to correctly understand the clinical signs of an injury and to interprete a radiographic image of it, so as to decide upon the optimal treatment on time.